Advancing Adjuvants for Mycobacterium tuberculosis Therapeutics - Enriquez, Ana B.; Izzo, Angelo; Miller, Shannon M.; Stewart, Erica L.; Mahon, Robert N.; Frank, Daniel J.; Evans, Jay T.; Rengarajan, Jyothi; Triccas, James A. (Frontiers in Immunology, 2021)
Tuberculosis (TB) remains one of the leading causes of death worldwide due to a single infectious disease agent. BCG, the only licensed vaccine against TB, offers limited protection against pulmonary disease in children and adults. TB vaccine research has recently been reinvigorated by new data suggesting alternative administration of BCG induces protection and a subunit/adjuvant vaccine that provides close to 50% protection. These results demonstrate the need for generating adjuvants in order to develop the next generation of TB vaccines. However, development of TB-targeted adjuvants is lacking. To help meet this need, NIAID convened a workshop in 2020 titled “Advancing Vaccine Adjuvants for Mycobacterium tuberculosis Therapeutics”. In this review, we present the four areas identified in the workshop as necessary for advancing TB adjuvants: 1) correlates of protective immunity, 2) targeting specific immune cells, 3) immune evasion mechanisms, and 4) animal models. We will discuss each of these four areas in detail and summarize what is known and what we can advance on in order to help develop more efficacious TB vaccines.